The effectiveness of therapy for endometriosis-associated pelvic pain resistant to surgical treatment - Mekan R. Orazov (IP Berlin A.V., 2021)
Aim. To assess the efficacy and safety of 24-week therapy with dienogest in patients with endometriosis-associated pelvic pain resistant to surgical treatment.